New Method For Optimal For Transportation Problem (Aditya’s Method) - S. Aditya Krishnan (International Journal of Mathematics And its Applications, 2018)
The main aim of this paper is to provide a new method (Aditya's Method) to obtain the optimal solution for transportation by skipping the modi method and obtain the correct result.